DEVELOPMENT OF NEW, GREEN, AND RAPID METHOD FOR THE DETECTION OF SPORTS-PROHIBITED DRUG FLUTICASONE PROPIONATE IN BLOOD (Journal of Forensic Medicine & Toxicology, 2025)
Fluticasone propionate (FP) is an extensively used synthetic tri-fluorinated glucocorticosteroid receptor beta-2-agonist. It is considered a sports-prohibited drug by the World Anti-Doping Agency (WADA). These drugs are being rapidly abused through various forms of medicines nasal sprays, inhalers, and topical treatments for various inflammatory issues. In this study, a new, green, rapid, and cost-effective method was established and authenticated for the detection and quantification of FP. The desired analyte was extracted from a real sample (blood) using ultrasonicator-assisted dispersive liquid liquid microextraction. The extractant from the DLLME was quantized using thin-layer chromatography in which the mobile phase of acetic acid: ethyl acetate: n-hexane (0.2:10:5) was used. The developed plate was photographed using a digital camera under a UV chamber (254 nm). The image was detected by using ImageJ software for the quantification of FP. Under optimized conditions, the method validation for blood samples was linear from 0.93 to 7.50 µg/spot for FP, with a correlation coefficient (R2) range from 0.995. The LOD and LOQ were in the range of 0.93 and 1.87 µg/spot were found to be 0.34 and 1.09. The relative recovery of the analyte from the blood sample was 94.74%. Also, the greenness of the method developed was calculated with Agree and GAPI software. Hence, it is suggested that the
Keywords: Fluticasone propionate; micro-extraction; US-DLLME; thin layer chromatography; image analysis.